Evaluation of the potassium adsorption capacity of a potassium adsorption filter during rapid blood transfusion. Issue 4 (6th March 2015) - Matsuura, H.; Akatsuka, Y.; Muramatsu, C.; Isogai, S.; Sugiura, Y.; Arakawa, S.; Murayama, M.; Kurahashi, M.; Takasuga, H.; Oshige, T.; Yuba, T.; Mizuta, S.; et al.
<x xml:space="preserve">Abstract</x> The concentration of extracellular potassium in red blood cell concentrates (RCCs) increases during storage, leading to risk of hyperkalemia. A potassium adsorption filter (PAF) can eliminate the potassium at normal blood transfusion. This study aimed to investigate the potassium adsorption capacity of a PAF during rapid blood transfusion. We tested several different potassium concentrations under a rapid transfusion condition using a pressure bag. The adsorption rates of the 70‐mEq/l model were 76·8%. The PAF showed good potassium adsorption capacity, suggesting that this filter may provide a convenient method to prevent hyperkalemia during rapid blood transfusion.